Maria Ahn, Xavier Espluga & Alejandra Guzmán (eds.), «Pere Miquel Carbonell i el seu temps (1434-1517)», Barcelona, Reial Acadèmia de Bones Lletres, 2016, 252 pp. - Martínez Mayor, Carlos (Caplletra. Revista Internacional de Filologia, 2018)
Ressenya sobre el llibre de Maria Ahn, Xavier Espluga & Alejandra Guzmán (eds.), «Pere Miquel Carbonell i el seu temps (1434-1517)», Barcelona, Reial Acadèmia de Bones Lletres, 2016, 252 pp., ISBN: 978-84-945234-0-3.